2009
DOI: 10.1371/journal.pgen.1000450
|View full text |Cite
|
Sign up to set email alerts
|

A Regulated Response to Impaired Respiration Slows Behavioral Rates and Increases Lifespan in Caenorhabditis elegans

Abstract: When mitochondrial respiration or ubiquinone production is inhibited in Caenorhabditis elegans, behavioral rates are slowed and lifespan is extended. Here, we show that these perturbations increase the expression of cell-protective and metabolic genes and the abundance of mitochondrial DNA. This response is similar to the response triggered by inhibiting respiration in yeast and mammalian cells, termed the “retrograde response”. As in yeast, genes switched on in C. elegans mitochondrial mutants extend lifespan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
142
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 41 publications
13
142
2
2
Order By: Relevance
“…S3 and SI Appendix, Table S2. (17,43) in which gene-expression patterns of isp-1 mutants were compared with those of wild-type animals ( Table 1 and Dataset S1). Among the differentially regulated genes in our dataset (q < 0.05, Dataset S1), smf-3 and ftn-1 were intriguing, because these genes are implicated in the regulation of cellular levels of iron ions and ROS.…”
Section: Hif-1 May Mediate Ros-induced Longevity By Regulating Ironmentioning
confidence: 99%
“…S3 and SI Appendix, Table S2. (17,43) in which gene-expression patterns of isp-1 mutants were compared with those of wild-type animals ( Table 1 and Dataset S1). Among the differentially regulated genes in our dataset (q < 0.05, Dataset S1), smf-3 and ftn-1 were intriguing, because these genes are implicated in the regulation of cellular levels of iron ions and ROS.…”
Section: Hif-1 May Mediate Ros-induced Longevity By Regulating Ironmentioning
confidence: 99%
“…Studies on the model organism C. elegans have revealed that perturbation in mitochondrial respiration and ROS induction can in fact have protective effects and lifespan extending properties. 30,31 Similarly, antioxidant treatments were found to abolish the positive metabolic effects (increase in insulin sensitivity) of exercise in humans. 32 Further studies are required to determine the potential of ROS and ROS signalling components for the treatment and prevention of age associated diseases and pathologies.…”
Section: Ros Induced Dna Damage and Checkpoint Responsesmentioning
confidence: 99%
“…Dietary restriction shifts metabolism toward respiration (Lin et al., 2002) but, at the same time, impaired respiration can promote longevity in yeast and nematodes through enhanced retrograde response and activation of anaplerotic pathways (Cristina, Cary, Lunceford, Clarke & Kenyon, 2009). Although we did not follow up on this intriguing observation, we speculate that a higher demand for respiration during dietary restriction could lead to the activation of compensatory pathways.…”
Section: Resultsmentioning
confidence: 99%